Aptamer-nanoparticle bioconjugates enhance intracellular delivery of vinorelbine to breast cancer cells. (January 2014) - Zhou, Wenhu; Zhou, Yanbin; Wu, Jianping; Liu, Zhenbao; Zhao, Huanzhe; Liu, Juewen; Ding, Jinsong
Abstract Targeted uptake of therapeutic nanoparticles in cell- or tissue-specific manner is an attractive technology since they can offer greater efficacy and reduce cytotoxicity on peripheral healthy tissues. In this study, AS1411 (AP), a DNA aptamer specifically binding to nucleolin that is overexpressed on the plasma membrane of breast cancer (BC) cells, was exploited as the targeting ligand of a nanoparticle-based drug delivery system. Vinorelbine (VRL) loaded PLGA-PEG nanoparticles (NP) were formulated by an emulsion/solvent evaporation method, and AP was conjugated to the particle surface using the EDC/NHS technique. The drug-loading efficiency and in vitro drug release studies were measured using HPLC. The resulting AP−NP/VRL formed spherical nanoparticles (<200 nm) with drug loading of about 7% and a stable in vitro drug release profile. Fluorescence microscopy was used to confirm the cellular uptake of the particles and targeted drug delivery. Moreover, cytotoxicity studies were carried out in two different cell lines, MDA-MB-231 BC cells and MCF-10A normal epithelial cells. AP-nucleolin interaction significantly enhanced in vitro cytotoxicity to nucleolin overexpressed cells, as compared with non-targeted nanoparticles, while there was no significant difference in cytotoxicity of the two types of nanoparticles on the nucleolin negative cells. The results further support that AS1411-functionalized nanoparticles are potential carrier candidates for targeted drug delivery towards BC.